Effect of Pyrite Ore in Direct Coal Liquefaction Process - G. Santos, Felipe; G. Riella, Humberto; Ana P. M. Martins, Maria; Vieira, Ricardo (Current Catalysis, 2014)
The catalytic activity of pyrite ore from coal mining was studied in the direct liquefaction process of high volatile bituminous coal from the south of Brazil. The process consisted of mixing pulverized coal with tetralin in the presence of catalyst. It was possible to obtain fractions of preasphaltenes, asphaltenes, and oils. Pressure had little influence on the direct coal liquefaction process, while temperature had a strong effect on liquefaction yields. The results of total conversions obtained were nearly 16 % at 300 °C, 26.5 % at 350 °C and 38.5 % at 380 °C, in spite of high inertinite-group maceral content (34 vol.%). The pyrite ore catalyst had a fundamental role in this reaction, leading to thermal cracking of the coal structure and hydrogenation of the fragments. However, the most significant result related to catalyst presence was the increase in selectivity of the oil fraction.
Keywords: direct coal liquefaction